Drying Behaviour of 50 mm Thick Turkey Oak Lumber - Deaconu, Iulia-Teodora; Georgescu, Sergiu-Valeriu; Campean, Mihaela (MDPI AG, 2023)
Turkey oak lumber is difficult to dry being prone to cracks even at low temperatures. The main objective of the research was to test different drying conditions in order to establish: whether air-drying or kiln-drying from green state is more suitable; if the lumber width has an influence on the drying quality, if prior steaming has a positive effect upon the kiln-drying time and quality, if end cracks can be avoided by protecting the board ends; and what the most appropriate kiln-drying conditions are, with conventional drying. The research results recommend kiln-drying as a better alternative than air-drying both in terms of time and quality, but very mild conditions must be applied. Wide lumber parts cracked both when air-dried and when kiln-dried. All defect-free lumber parts dried accurately, with no deterioration. Steaming had a positive effect upon the drying quality; no steamed part cracked. The end-protection of the boards was efficient only in the case of kiln-drying.
Keywords: Turkey oak; air drying; kiln drying; drying time; drying quality